1975
DOI: 10.1172/jci108234
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietic protoporphyria and lead intoxication: the molecular basis for difference in cutaneous photosensitivity. II. Different binding of erythrocyte protoporphyrin to hemoglobin.

Abstract: A B S T R A C T Acidic solvenits extract the same porphyrin-protoporphyrin-from the erythrocytes of patients with either erythropoietic protoporphvria or lead intoxication. However, extractable protoporplhyrin disappears rapidly, both in vivo alnd in vitro, frolmi ervthrocytes in erythropoietic protoporphyria but slowly, if at all, in lead intoxicationi. Consistent w-ith these observations, fluorescence spectroscopy revealed that the intracellular state of the erythrocyte protoporphyrin is different in the two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
1

Year Published

1977
1977
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(37 citation statements)
references
References 18 publications
(15 reference statements)
0
36
0
1
Order By: Relevance
“…The patient was a 12-yr-old white girl, with the cutaneous photosensitivity characteristic of EPP. Protoporphyrin concentrations in her erythrocytes, plasma, and stool were markedly elevated (Table 1), and erythrocyte porphyrins consisted almost exclusively of free, not Zn-chelated, protoporphyrin (13). Ferrochelatase activity, as determined by an assay based on the ability of lymphocytes to form protoporphyrin from its precursor, 6-aminolevulinic acid (6), indicated that the proband's enzyme activity was about one-half (46.5%) the normal level (Table 1).…”
mentioning
confidence: 99%
“…The patient was a 12-yr-old white girl, with the cutaneous photosensitivity characteristic of EPP. Protoporphyrin concentrations in her erythrocytes, plasma, and stool were markedly elevated (Table 1), and erythrocyte porphyrins consisted almost exclusively of free, not Zn-chelated, protoporphyrin (13). Ferrochelatase activity, as determined by an assay based on the ability of lymphocytes to form protoporphyrin from its precursor, 6-aminolevulinic acid (6), indicated that the proband's enzyme activity was about one-half (46.5%) the normal level (Table 1).…”
mentioning
confidence: 99%
“…Ferrochelatase is responsible for the incorporation of iron into protoporphyrin IX to form heme. As a result of inhibition, protoporphyrin accumulates in erythrocytes, with the majority binding to zinc and to form zinc protoporphyrin [6]. Table 3 shows the various symptoms associated with lead poisoning in the two groups.…”
Section: Resultsmentioning
confidence: 99%
“…This is also the case in iron deficiency anemia (133). In both lead absorption and iron deficiency, it is the Zn chelate of protoporphyrin that accumulates (133,134) while in EPP it is mainly the free, basic form of protoporphyrin (134). The Zn chelate is bound to the heme site on hemoglobin, while the basic form is bound to nonheme sites (134).…”
Section: Ppe (Fep) Erythrocyte Protoporphyrin and Freementioning
confidence: 98%
“…In both lead absorption and iron deficiency, it is the Zn chelate of protoporphyrin that accumulates (133,134) while in EPP it is mainly the free, basic form of protoporphyrin (134). The Zn chelate is bound to the heme site on hemoglobin, while the basic form is bound to nonheme sites (134). Acidic organic solvents are used to extract "free" erythrocyte prophyrins (free of the Zn), while the intact Zn chelate can be extracted with acetone, ethanol or the detergent Ammonyx-LO (134).…”
Section: Ppe (Fep) Erythrocyte Protoporphyrin and Freementioning
confidence: 99%